Etiological Spectrum and Clinical Profile of Lower Gastrointestinal Bleed in a Tertiary Care Center: A Retrospective Analysis - Jain, Mukesh K.; Pandey, Vivek; Singh, Shashank; Gupta, Gaurav; Pokharna, Rupesh K. (Journal of Digestive Endoscopy, 2025)
Gastrointestinal (GI) bleeding is one of the most frequently encountered medical and surgical emergencies in gastroenterology practice. The etiology and epidemiology of lower gastrointestinal bleeding (LGIB) vary with age and are influenced by factors such as lifestyle, smoking habits, medication history, and the aging population. The underlying causes of LGIB differ across age groups, with distinct patterns observed in pediatric, adult, and elderly populations. This study aimed to evaluate the etiological and clinical spectrum of LGIB in a tertiary referral center.This was a single-center, cross-sectional retrospective study conducted in the Department of Gastroenterology at a leading tertiary referral center in northwest India. A total of 1,000 patients who presented with LGIB and underwent colonoscopic evaluation were included in the study.Of the 1,000 patients included in the study, 702 (70.2%) were male and 298 (29.8%) were female, with a male-to-female ratio of 2.35:1. A total of 678 (67.8%) patients were below 60 years of age, whereas 322 (32.2%) were aged 60 years and above. The most common presenting symptom was hematochezia, observed in 658 (65.8%) patients. Stool occult blood was positive in 26 (2.6%) cases.The most frequent colonoscopic finding was colitis—characterized by loss of vascular pattern, erosions, and ulcerations—seen in 287 (28.7%) patients. This was followed by hemorrhoids in 259 (25.9%), ulceroproliferative growths in 217 (21.7%), and isolated ulcers in 71 (7.1%).The leading etiology of LGIB was hemorrhoidal bleeding, accounting for 259 (25.9%) patients, followed by colorectal carcinoma (CRC) in 185 (18.5%), inflammatory bowel disease in 139 (13.9%), solitary rectal ulcer syndrome (SRUS) in 65 (6.5%), radiation proctitis in 49 (4.9%), infectious colitis in 41 (4.1%), and GI tuberculosis in 29 (2.9%). The overall diagnostic yield of colonoscopy in this study was 86.7%.LGIB is a common clinical presentation and a frequent cause of hospital visits. It may present overtly with hematochezia or manifest as occult bleeding, often resulting in anemia. The clinical presentation and underlying etiology vary based on age, sex, geographic location, and comorbid conditions. In India, anorectal causes such as hemorrhoids and SRUS are the most common etiologies of LGIB, followed by CRC. Colonoscopy remains the primary and most valuable diagnostic tool for evaluating patients with LGIB.
Keywords: angioectasia; lower gastrointestinal bleeding; colitis; colorectal carcinoma; inflammatory bowel disease; solitary rectal ulcer syndrome; ulcerative colitis; upper gastrointestinal bleeding; colonoscopy